A Cross-Sectional Study on Ultrasonographic Measurements of Parotid Glands in Type 2 Diabetes Mellitus - Abhishek Gupta; Vijayalakshmi Kondajji Ramachandra; Mubeen Khan; Kumari Sonam Jha; K. S. Vedaraju; Nirmala Alagudu Channaiah (International Journal of Dentistry)
Background. Diabetes mellitus is a metabolic disease which is seen increasing globally and is diagnosed and monitored on basis of invasive blood investigations. Salivary glands are affected in diabetes mellitus. The objective of this study was to assess ultrasonographic measurements of parotid glands and correlate with the glycosylated hemoglobin levels in type 2 diabetic mellitus and duration of type 2 diabetic mellitus and treatment regimens. Materials and Methods. This study was conducted on 50 subjects of type 2 diabetes mellitus and on 50 healthy controls. After HbA1C analysis of selected individuals, 100 individuals were grouped into group I (above 5.7) and group II (below 5.7). Ultrasonographic measurements (length (L), transverse dimension (TD), depth lateral to the mandible (DLM), and depth dorsal to the mandible (DDM)) of bilateral parotid glands were calculated. Statistical analysis was done using the chi-square test of significance and Spearman correlation coefficients. Results. On correlation with measurement of right (L, DLM, DDM) and left (TD, DLM, DDM) of parotid glands with duration of type 2 diabetes mellitus, we found a moderate positive relationship, whereas as for right (TD) and left (L), we found a low-positive relationship. Similarly, for right (L, TD, DLM, DDM) and left (TD, DDM) parotid glands with HbA1C, we found a low-positive relationship, whereas for left parotid gland (L, DLM) with HbA1C, we found a moderate positive relationship. The mean DLM of right and left parotids in the insulin group was found to be slightly more than that in the combined group which was statistically insignificant. Conclusion. Ultrasonographic measurements of parotid glands were found to be higher in study subjects as compared to control subjects, and they increased with increased HbA1C levels; also, there was no difference in treatment regimen. Ultrasonography could be a prospective diagnostic test for detection and monitoring of diabetes mellitus, and still further studies are required for this.